A função social da escola: uma análise das significações constituídas pelos gestores, professores, pais e alunos de uma escola pública paulista - Gomes, Alessandra de Oliveira Capuchinho (2014)
This study aimed at analyzing the meanings produced by the management team, professors, employees, parents and students regarding the school‟s social function. The theoretical reference adopted was that of Social-Historical Psychology. The research was performed at a State Elementary School in São Paulo located in the district of Brasilândia. After talking with the management team, it was defined that the participants of the research would be three members of the management team: the principle, vice-principle and pedagogical coordinator, two second-grade teachers, one third-grade teacher, two employees and ten third-grade children. As strategies to obtain the information, semi-structured interviews were used with the management team, teachers and employees, a questionnaire with open questions and closed answers was used with the students‟ parents and conversation sessions were used with the children. In the data analysis, Aguiar e Ozella‟s (2013) meaning core proposal was employed. It was possible to identify that the meanings of the management team, teachers and employees pertaining to the school‟s social function are strongly marked by the children and their families‟ naturalization and stigmatized conception. It was also detected that all research subjects have a conception of the school‟s social function strongly linked to an institution that has as its main objective the transmission of knowledge and education that enable the children to have a profession. Moreover, the school was seen as being the only possibility to reach better life conditions in the future. Although this study approaches matters of a determined school reality, it is possible to broaden this issue to the challenges concerning educational matters, especially those of the public school inserted in underprivileged suburbs of Brazilian cities